EFFECTIVENESS OF CHITOSAN NANOPARTICLE CONTAINING 0.7% TETRACYCLINES ON CLINICAL PARAMETERS AND FIBROBLAST GROWTH: FACTOR-2 IN RAT MODELS - SILVIA; ERVINA, IRMA; AMALIA, MARTINA; NASUTION, ERDI EFFENDI; AGUSNAR, HARRY; WULANDARI, PITU; NASUTION, RINI OCTAVIA (International Journal of Applied Pharmaceutics, 2024)
Objective: Tetracyclines in periodontitis improved probing depth, increased attachment level, and reduced bacterial colonies. Chitosan nanoparticles have slower drug release, better drug stability, and lower toxicity. This study is to evaluate the effectiveness of subgingival application of chitosan nanoparticles containing 0.7% tetracyclines in the periodontitis model on clinical parameters and fibroblast growth factor-2 (FGF-2) expression. Methods: Laboratory experimental research on 29 Wistar rats induced by p. gingivalis with pretest posttest control group design, divided into 4 treatment groups, 2 placebo groups, and 1 negative control group. Clinical parameters of bleeding on probing (BOP) and Pocket Depth (PD) and FGF-2 expression were evaluated on day 3 and 8. Results: Significant decrease in BOP was only found in the daily application group of chitosan nanoparticles containing 0.7% tetracyclines on day 8 (p=0.008) and significant decrease in mean PD was found in the application group of chitosan nanoparticles containing 0.7% tetracyclines every day (p=0.034) or once only (p=0.046). FGF-2 expression increased on day 3 of each group and decreased on day 8 of each group. Significant difference in the FGF-2 expression was found in all groups on day 3 (p=0.034) but it was only between the daily application group and the once only application group (p=0.012). Conclusion: There was a decrease in the percentage of BOP and PD in all groups as well as a significant increase in FGF-2 expression on day 3 and 8 after the application of chitosan nanoparticles containing 0.7% tetracyclines.